Maternal Vitamin D Deficiency and the Risk of Small for Gestational Age: A Meta-analysis - Zhao HU; Lu TANG; Hui-Lan XU (Tehran University of Medical Sciences, 2018)
Background: Inconsistencies among studies still exist in regard to the associations between maternal vitamin D deficiency and the risk of small for gestational age. Methods: We conducted a meta-analysis of observational studies to evaluate these associations. We searched electronic databases for literature published in PubMed, Medline, Web of Science, Embase and the Cochrane Library up to Dec 2016 using the following keywords: "vitamin D" or "cholecalciferol" or "25-OHD" or "25-hydroxyvitamin D" in combination with "small for gestational age" or "SGA" or "fetal outcome" or "pregnancy outcome".  Results: Twelve studies involving 19,027 participants were included in this meta-analysis. Pregnant women with vitamin D deficiency (25-OHD levels<50 nmol/L) experienced an increased risk of SGA (odds ratio (OR) =1.41, 95% confidence interval (CI): 1.14, 1.75). The vitamin D concentration of the SGA group was lower than that of the non-SGA group (mean difference: -1.75 nmol/L, 95%CI:-3.23, -0.27). Conclusion: Maternal vitamin D deficiency during pregnancy may be associated with an increased risk of SGA.